Why do students decide to study culinary arts and why don't they maintain interest in the hotel industry employment? / Fadzillah Mohd Shariff, Mohd Zain Kutut and Hamizad Abdul Hadi - Mohd Shariff, Fadzillah; Kutut, Mohd Zain; Abdul Hadi, Hamizad (2014)
This paper reports the results of the research project (IRDC) into factors influencing students in advancing education in culinary arts at Faculty of Hotel and Tourism Management, UiTM. In other words, this study examines the moderating variables that influence a student decision to enter Culinary Arts program and subsequent interest towards industry employment. All students who enrolled at three levels of the Diploma culinary arts program (part one of first year, part three of second year and part five of third year) from Shah Alam, Penang and Dungun campuses was surveyed at the beginning of the semester and followed them through a second round survey at the beginning of another semester. Students' career choice and the decision of taking culinary arts program are influenced by various factors ranging from parents, immediate family, and glamorous image to advertisement on television, brochures, and newspaper. Among all, parents are found to be the strongest influence on the individual students' decision. Nevertheless, despite continuous encouragement, many students are becoming less positive in interest toward employment in the hotel industry and reduced intention to pursue such a career. These weakened employment intentions have given varying consequences and implications for the students, hospitality institutions, industry, and government.